International Trade and Green Growth - Copeland, Brian R. (World Bank, Washington, DC, 2013)
This paper reviews the challenges and opportunities raised by international trade for developing countries considering a green growth strategy. A key concern is the effect of environmental policies on international competitiveness. For production-generated pollution, there is evidence that stringent environmental policy reduces some indicators of competitiveness, but the effect is small in most sectors. However, tightening up environmental standards is unlikely to reduce international competitiveness when pollution is generated by consumption. And where depletion of natural capital is a threat, effective environmental policy is an important component of a policy aimed at developing long-run international competitiveness. The effects of trade on environmental policy, the interaction between trade and technology transfer, and the interaction between trade and transboundary environmental problems are also reviewed. An emerging issue is the potential use of border taxes to curtail carbon leakage. The paper discusses some of the possible responses by developing countries. Some work has indicated that export taxes or voluntary export restraints applied to carbon-intensive production in non-coalition countries may be preferable to a carbon tariff regime. The paper concludes by suggesting some topics for further research.